The weight of biodiversity in the national decision-making concerning the strict protection of all remaining old-growth forests : a comparative analysis of EU Forest Strategy implementation in Finland and Sweden - Ihalainen, Fanni (My University, 2024)
This thesis sheds light on the aim in the EU Forest Strategy of strictly protecting all remaining old-growth forests in the EU. The overarching goal of this thesis is to illuminate the preparation phase of the implementation of this goal in two EU member states, Finland and Sweden, and which weight the preservation of biodiversity receives in this process. The research is carried out with the methods of comparative legal research. The theoretical framework of this study is a combination of the functional-institutional approach and the law-in-context approach. Through the chosen theoretical framework, this research compares the institutional processes where the national definitions of old-growth forests are prepared. National preparatory documents are analysed with thematic analysis to identify the national motivations and review, what is their relation to biodiversity preservation. Through the law-in-context approach, this research aims to identify how different societal elements and needs affect how biodiversity is considered in the national decision-making. This research shows that the processes of developing national definitions for old-growth forests have followed similar steps in both Finland and Sweden. However, some significant differences emerge: in Sweden, a report prepared by officials includes some established definitions of old-growth forests, which may indicate that this stage of the national process holds more influence. This might allow Swedish decision-making to be more grounded in previous research about old-growth forests. In Finnish decision-making, the imperative role of politics is openly acknowledged, in contrast to Sweden. Thematic analysis of the national preparatory documents reveals that themes in the documents of both countries might reflect societal interests that could conflict, potentially diminishing the importance of biodiversity considerations or leaving the importance that biodiversity receives unclear.

Tämä tutkielma luo katsauksen EU:n metsästrategian kaikkien jäljellä olevien vanhojen metsien tiukan suojelun tavoitteeseen. Tutkielman tavoite on valaista toteuttamisen valmisteluvaihetta kahdessa EU:n jäsenmaassa, Suomessa ja Ruotsissa, erityisesti keskittyen siihen, minkä painoarvon biodiversiteetin suojelu saa tässä prosessissa. Tutkimus toteutetaan vertailevan oikeustutkimuksen menetelmillä. Tämän tutkimuksen teoreettinen viitekehys on yhdistelmä funktionaalis-institutionaalista lähestymistapaa ja law-in-context -lähestymistapaa. Valitun teoreettisen viitekehyksen kautta tämä tutkimus vertailee kansallisia institutionaalisia prosesseja, joissa kansallisia määritelmiä vanhoille metsille valmistellaan. Kansallisia virallisia valmisteluasiakirjoja käydään läpi temaattisen analyysin avulla sen tunnistamiseksi, millaisia kansallisia motivaatioita EU:n metsästrategiaan liittyen esitetään, ja miten ne suhteutuvat biodiversiteetin suojeluun. Law-in-context -lähestymistavan kautta tämä tutkimus pyrkii tunnistamaan, kuinka erilaiset yhteiskunnalliset elementit ja tarpeet vaikuttavat siihen, minkä painoarvon biodiversiteetin suojelu saa kansallisessa päätöksenteossa. Tutkimus osoittaa, että prosessit, joissa kansallisia määritelmiä vanhoille metsille valmistellaan, ovat edenneet samankaltaisin askelin sekä Suomessa että Ruotsissa. Muutamia merkittävä eroja kuitenkin on: Ruotsissa viranomaisten valmistelema raportti sisältää valmiin määritelmän vanhasta metsästä. Tämä voi tarkoittaa, että tämä vaihe kansallisessa prosessissa on Ruotsissa vaikutusvaltaisempi, mistä voi seurata, että ruotsalainen päätöksenteko voi perustua vahvemmin aikaisempaan tutkimukseen vanhoista metsistä. Toisin kuin Ruotsissa, Suomalaisessa päätöksenteossa politiikan määräävä rooli on avoimesti tunnustettu. Kansallisten valmisteluasiakirjojen läpikäynti temaattisella analyysilla paljastaa, että molemmissa valtioissa teemat heijastavat yhteiskunnallisia intressejä, jotka voivat olla ristiriitaisia suhteessa toisiinsa mahdollisesti vähentäen biodiversiteetin painoarvoa tai jättäen biodiversiteetin aseman epäselväksi.
Keywords: biodiversity, European Union, EU Forest Strategy, EU Biodiversity Strategy, primary and old-growth forests, sustainable forest management, national economy, comparative legal research, thematic analysis, functional-institutional approach, law-in-context approach, biodiversiteetti, luonnon monimuotoisuus, Euroopan Unioni, EU:n metsästrategia, EU:n biodiversiteettistrategia, luonnontilaiset ja vanhat metsät, kestävä metsien käyttö, kansantalous, vertaileva oikeustutkimus, temaattinen analyysi, funktionaalis-institutionaalinen lähestymistapa, law-in-context -lähestymistapa